2013
DOI: 10.4103/0972-5229.117041
|View full text |Cite
|
Sign up to set email alerts
|

Infective endocarditis in an Indian setup: Are we entering the ′modern′ era?

Abstract: Background:The clinical profile of infective endocarditis (IE) has been continuously evolving over last 3-4 decades as highlighted by many studies from developed world.Objectives:To evaluate the recent changes in the spectrum and clinical profile, and outcome of IE in an Indian setup.Materials and Methods:This was a descriptive, cross-sectional study. Demographic, clinical, characteristics, treatment, and outcome were examined in ‘definite’ cases of IE admitted at our institute between July 2005 and December 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
24
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 32 publications
2
24
0
Order By: Relevance
“…Staphylococcus accounts for 15-50% of cases with Staphylococcus aureus more common than coagulase negative Staphylococcus (CoNS). [19][20][21][22][23]25,31,32,34 Comparison with pre-millennial ranges shows an increase in Staphylococcus which was previously reported in less than 20% of cases. 11,13,28 The emergence of Staphylococcus as a leading cause of IE in LMICs, a trend that was also previously noted in HICs, may reflect medical technology advances, increased hospital contact and increasing comorbidities.…”
Section: Staphylococcusmentioning
confidence: 60%
See 4 more Smart Citations
“…Staphylococcus accounts for 15-50% of cases with Staphylococcus aureus more common than coagulase negative Staphylococcus (CoNS). [19][20][21][22][23]25,31,32,34 Comparison with pre-millennial ranges shows an increase in Staphylococcus which was previously reported in less than 20% of cases. 11,13,28 The emergence of Staphylococcus as a leading cause of IE in LMICs, a trend that was also previously noted in HICs, may reflect medical technology advances, increased hospital contact and increasing comorbidities.…”
Section: Staphylococcusmentioning
confidence: 60%
“…[19][20][21][22][23][24] Nel et al 25 however, reported a much higher (78%) prevalence of underlying RHD in their study in South Africa, a country where RHD is endemic. 26 Overall, this range of underlying RHD in IE represents a decline from the 45-80% reported in earlier (pre-2000) LMIC studies.…”
Section: Underlying Cardiac Conditionsmentioning
confidence: 77%
See 3 more Smart Citations